2005
DOI: 10.1038/labinvest.3700275
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 is expressed in hepatic stellate cells

Abstract: ADAMTS13 is a circulating zinc metalloprotease that cleaves the hemostatic glycoprotein von Willebrand factor (VWF) in a shear-dependent manner. Deficiency in ADAMTS13, owing to genetic mutations or autoimmune inhibitors, causes thrombotic thrombocytopenic purpura (TPP). Northern blot analysis has shown that ADAMTS13 is expressed primarily in the liver. By using real-time RT-PCR, we confirmed that in mice the liver had the highest level of the ADAMTS13 transcript. To identify the liver cell-type-specific origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
126
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 24 publications
0
126
0
3
Order By: Relevance
“…With regard to the site of production, ADAMTS13 mRNA expression was shown exclusively in the liver (7)(8)(9) and then both ADAMTS13 mRNA expression and ADAMTS13 activity were determined primarily in hepatic stellate cells among the liver cells in mice (10). ADAMTS13 expression was also detected in hepatic stellate cells in human and thereby ADAMTS13 is reportedly produced in those cells (11).…”
Section: Introductionmentioning
confidence: 92%
“…With regard to the site of production, ADAMTS13 mRNA expression was shown exclusively in the liver (7)(8)(9) and then both ADAMTS13 mRNA expression and ADAMTS13 activity were determined primarily in hepatic stellate cells among the liver cells in mice (10). ADAMTS13 expression was also detected in hepatic stellate cells in human and thereby ADAMTS13 is reportedly produced in those cells (11).…”
Section: Introductionmentioning
confidence: 92%
“…Under physiological conditions, VWF size is partly regulated by the constitutively active blood metalloprotease, a disintegrin and metalloprotease with thrombospondin type 1 motif 13 (ADAMTS13). [2][3][4] This protease is secreted into blood by hepatic stellate cells 3,5,6 and is also synthesized by ECs [7][8][9] and platelets. 10,11 ADAMTS13 cleaves the Tyr1605-Met1606 scissile bond located within the A2-domain of VWF (VWF-A2) that is exposed upon the application of fluid/hydrodynamic shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…It encodes a 4.7-kb transcript that is expressed primarily in the stellate cells of the liver and a 2.4-kb transcript detectable in multiple tissues including placenta, skeletal muscle, and certain tumor cell lines (4)(5)(6)(7)(8). Some investigators have reported that ADAMTS13 may also be expressed in platelets and cultured endothelial cells (9)(10)(11).…”
Section: Pathophysiology Of Ttp Vwf and Adamts13mentioning
confidence: 99%